What can linguistics tell us about early Khoekhoe history? - Heine, B.; König, C. (Southern African Humanities, 2021)
Linguistic evidence has played some role in the debates that have taken place on early Khoekhoe history, but it has also been a source of conjectural reasoning, starting with the Hamitic hypothesis and continuing with speculations on migrations and early history. Compared to such work the present paper might seem destructive, in that it ignores all the fascinating hypotheses that have been and are being proposed by linguists - hypotheses that sometimes have been taken by non-linguists to reflect reconstructions based on a sound empirical foundation. As will be argued in this paper, such a foundation does not exist in most of the cases concerned. To cite this article: Heine, B. & König, C. 2008. What can linguistics tell us about early Khoekhoe history? Southern African Humanities 20: 235-48.